(untitled) (Research, Society and Development, 2022)
This bibliographical research problematizes administrative practices developed by civil servants occupying positions of the Administrative Technician in Education career at the Federal Institute of Alagoas who have administrative law as a basis, linked to other transversal themes. Our research question asks whether through the promotion of knowledge of administrative law it is possible to provide internal operational and social transformations to overcome existing administrative operational mistakes. The main objective is to reflect on whether the assimilation of basic knowledge of administrative law will provide a better development of administrative practices and will contribute to the construction of critical knowledge about the area, the attributions of their positions and the sector, provoking reflections and changes in individual and of the teams. The results point to the contributions that the omnilateral training of civil servants provides for their professional self-recognition, generating a positive impact in the finalistic area; Teaching, Research and Extension; of the institution, considering that it needs the groundwork carried out by the technical teams to achieve the best development of the core activity.